Respostas
respondido por:
1
4x + 8 = -2x + 26
4x + 2x = 26 - 8
6x = 18
x = 3
4x + 2x = 26 - 8
6x = 18
x = 3
Anônimo:
marca ai como a melhor resposta fanny
respondido por:
0
Olá, boa noite ☺
Resolução:
4(x+2)=-2(x-13)
4x + 8 = -2x + 26.
4x + 2x = 26 - 8.
6x= 18.
x= 18/6.
x=3.
Bons estudos :)
Resolução:
4(x+2)=-2(x-13)
4x + 8 = -2x + 26.
4x + 2x = 26 - 8.
6x= 18.
x= 18/6.
x=3.
Bons estudos :)
Perguntas similares
6 anos atrás
6 anos atrás
6 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás